Sedentary Behaviour Epidemiology (Springer Series on Epidemiology and Public Health,, 2018)
This book addresses the origins, determinants and magnitude of the global problem of sedentary behaviour, along with concise yet in-depth solutions for tackling it. As a consequence of major technological advances in modern society, many people find themselves in environments characterized by prolonged sedentary behaviour. Although inadequate exercise has long been known to cause adverse health consequences, sedentary behaviour has recently emerged as a risk factor for the development of numerous chronic diseases and health conditions. Building on the contributions of leading experts in the field, this book presents current knowledge about sedentary behaviour, its medical and public health significance, its correlates and determinants, measurement techniques, and recommendations for addressing this behaviour at the individual, community, environmental, and policy level. Applying a cross-disciplinary methodology, the book avoids considering physical activity and sedentary behavior as a single continuum, which potentially hampers progress in confronting widespread levels of sedentariness. Rather, the book helps readers better understand how sedentary and physically active behavior co-occur and how the two behaviours have distinct contributing factors. Building on the contributions of distinguished international experts in the field, this thorough resource is a valuable asset and challenges professionals, researchers, students, and practitioners alike to adopt new strategies and expand their reach.